2016
DOI: 10.1007/s00436-016-5218-8
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of 25 synthetic insecticides to the field population of Culex quinquefasciatus Say

Abstract: The Culex quinquefaciatus Say, commonly known as the southern house mosquito, is well known for biting nuisance and vectoring of some fatal diseases. Synthetic chemicals have been relied upon as the major control measure to control mosquitoes. Therefore, we have evaluated 21 insecticides belonging to different chemical classes for their toxicity to C. quinquefaciatus females. Chlorfenapyr was the most toxic adulticide among all the tested insecticides. Among pyrethroids, deltamethrin was the least toxic adulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…The high percentage mortality of mosquitoes (60%) indicates that a high fraction of chlorpyrifos is released from clay and the commercial formulation and consequently their potential for leaching into the soil profile is high. These results are in accord with recent report Shah et al[53] who found that chlorpyrifos has been shown to be the most toxic insecticide against southern house mosquito (The Culex quinquefaciatus Say). In contrast, organo-clay formulations released a significantly lower fraction of chlorpyrifos and consequently a lower percentage mortality of mosquito larvae was observed.…”
supporting
confidence: 93%
“…The high percentage mortality of mosquitoes (60%) indicates that a high fraction of chlorpyrifos is released from clay and the commercial formulation and consequently their potential for leaching into the soil profile is high. These results are in accord with recent report Shah et al[53] who found that chlorpyrifos has been shown to be the most toxic insecticide against southern house mosquito (The Culex quinquefaciatus Say). In contrast, organo-clay formulations released a significantly lower fraction of chlorpyrifos and consequently a lower percentage mortality of mosquito larvae was observed.…”
supporting
confidence: 93%
“…With long residual ingestion activity on target arthropods and low toxicity to beneficial arthropods, EB is widely used for control of pest insects ( López et al, 2010 ). In previous research, EB exhibited ovicidal activity against Cydia molesta (Busck) (Lepidoptera: Tortricideae), larvicidal activity against Culex quinquefasciatus say (Diptera: Culicidae), and adulticidal activity against Cydia pomonella (L.) (lepidoptera: Tortricidae) ( Ioriatti et al, 2009 ; Wu et al, 2015 ; Shah et al, 2016 ). However, EB was reported to be a harmless insecticide for adults of Adalia bipunctata (L.) (Coleoptera: Coccinellidae), Coccinella transversalis (F.) (Coleoptera: Coccinellidae), and Macrolophus pygmaeus (Hemiptera: Miridae) ( Cole et al, 2010 ; Martinou et al, 2014 ; Depalo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…A susceptibility survey of 19 pesticides tested against insectary colonies of Aedes aegypti, Culex quinquefasciatus and Anopheles quadrimaculatus indicated that chlorfenapyr was most effective against An . quadrimaculatus and least against Culex quinquefasciatus [12]; other toxicity screens have reported that chlorfenapyr can have a lethal effect against field populations of the latter species [13]. Furthermore, multiple phase II trials in Tanzania and Benin have highlighted the effectiveness of chlorfenapyr as an adjunct to pyrethroid-treated nets against Anopheles arabiensis, Anopheles gambiae sensu stricto (s.s.), and Culex quinquefasciatus [1418] and as a candidate for IRS in Benin [8, 10].…”
Section: Introductionmentioning
confidence: 99%